Analysis of Scientific production aligned with the Food and Nutrition Security Strategy of Portuguese-Speaking African Institutions: a systematic scoping review - Miquitaio, Augusto Mário [UNESP]; Crisp, Alex Harley; Zuliani, Daniela Queiroz; de Moura, Ana Pinto; de Oliveira, Maria Rita Marques [UNESP] (FapUNIFESP (SciELO), 2023)
This systematic scoping review aimed to map and characterize the scientific production of researchers from Portuguese-speaking African institutions that align with the Food and Nutrition Security Strategy of the Community of Portuguese-Speaking Countries. The literature search was conducted using six electronic databases (PubMed, EMBASE, Virtual Health Library, Scientific Electronic Library Online, Scopus, and Web of Science), with no restrictions on the year of publication nor language. Through the search strategy, 10,061 records were identified, of which 502 documents and 654 researchers were selected by Food and Nutrition Security specialists along three axes: 1) Policy governance; 2) Access to food; 3) Availability of food. Institutional researchers from Mozambique (66.9%), Guinea-Bissau (15.9%), and Angola (11.4%) presented the most publications and international collaborations. Researchers from Cape Verde, Sao Tome and Principe, and Equatorial Guinea institutions added only 5.8% of the total production. A greater number of publications (61%) was related to axis two of the Food and Nutrition Security Strategy of the Community of Portuguese-Speaking Countries. The most studied themes were sustainable development, child malnutrition, and agricultural production for the first, second, and third axis, respectively. In general, scientific publications have shown limitations in their approaches due to the challenge imposed by the complexity of the food system. However, there has been a quantitative evolution in publications in the last decade, with a greater participation of researchers from Portuguese-speaking African institutions
Análise da produção científica alinhada com a Estratégia de Segurança Alimentar e Nutricional das Instituições Africanas de Língua Portuguesa: uma revisão sistemática de escopo
Keywords: Authorship and co-authorship in scientific publications; Food insecurity; Human rights